Model for Backyard Poultry Farming in West Bengal, India - Das, P.K.; Ghosh, P.R.; Roy, B.; Mazumdar, D. (International Journal of Poultry Science, 2013)
Family poultry is presently considered as a Special Programme for Food Security particularly at the developing countries in the world. In this outset, a study was conducted on 60000 Rhode Island Red (RIR) birds by twenty four major treatment types to identify the best combination of major inputs viz. age of birds, initial supply of concentrated feed upto grower stage followed by supplementation of ration produced by the farmers using locally available ingredients along with run space to develop a model on backyard poultry production system under scavenging at five agroclimatic zones in West Bengal, India where largest Poultry Distribution Scheme of world were implemented. Twenty one variables under three major criteria viz. production and physiological, economical and adoption of technology were considered as vital effect using factor analysis and linear indexing technique. The result showed that 21 day old bird may to be selected for sustainable backyard poultry farming through Rhode Island Red breed at all agroclimatic zone under study. It was shown that a run space of above 20 sq ft per bird with the provision of 50% quantity of commercial poultry ration as per their requirement before laying followed by supplementary feed having 10.01-15.00 g crude protein per day ranked first among 24 treatment groups. The best agroclimatic zone for backyard poultry farming is coastal zone. The best possible combination of input and supportive factor for economic backyard poultry farming at farmers’ doorstep of various agroclimatic zones was also analyzed.